2020
DOI: 10.1002/mc.23151
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of immune‐mediated bone marrow damage in conventionally housed mice

Abstract: In humans, bone marrow (BM) failure syndromes, both constitutional and acquired, predispose to myeloid malignancies. We have modeled acquired immune aplastic anemia, the paradigmatic disease of these syndromes, in the mouse by infusing lymph node (LN) cells from specific pathogen free (SPF) CD45.1 congenic C57BL/6 (B6) donors into hybrid CByB6F1 recipients housed either in conventional (CVB) or SPF facilities. Severity of BM damage was reduced in CVB recipients; they also had reduced levels of CD44 + CD62L − e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…Analysis of gut microorganisms revealed significant differences between CVT and SPF mice showing effective transfer of microorganisms from CVB to CVT mice through co-housing. The top three OTUs highly represented in CVB mice and effectively transferred to CVT mice during co-housing were Prevotellaceae, Lactobacillaceae and Rikenellaceae, which is consistent with our previous observation in CByB6F1 mice born and housed in the same conventional facility in which the same three microbial families were most abundant in CVB mice [17].These microbial families offer health benefits, since lack of Prevotellaceae and Rikenellaceae have been associated with Parkinson's disease [21], and liver cirrhosis [22]. In Rag1-/-mice, fecal transplants from wild type donors altered gut bacterial community with increases in Prevotellaceae which were accompanied by increases in total number of BM cells and HSPCs [23].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Analysis of gut microorganisms revealed significant differences between CVT and SPF mice showing effective transfer of microorganisms from CVB to CVT mice through co-housing. The top three OTUs highly represented in CVB mice and effectively transferred to CVT mice during co-housing were Prevotellaceae, Lactobacillaceae and Rikenellaceae, which is consistent with our previous observation in CByB6F1 mice born and housed in the same conventional facility in which the same three microbial families were most abundant in CVB mice [17].These microbial families offer health benefits, since lack of Prevotellaceae and Rikenellaceae have been associated with Parkinson's disease [21], and liver cirrhosis [22]. In Rag1-/-mice, fecal transplants from wild type donors altered gut bacterial community with increases in Prevotellaceae which were accompanied by increases in total number of BM cells and HSPCs [23].…”
Section: Discussionsupporting
confidence: 90%
“…Recapitulation of adult human immune traits in laboratory mice following co-housing with pet-store mice provided strong evidence showing that restoring physiological microbial exposure in laboratory mice could better model immunological events in humans [ 1 ]. Previously, we found that mice born and raised in a conventional facility (CVB) exert greater ability to suppress foreign T cell activation and to attenuate immune-mediated BM destruction than SPF-housed mice [ 17 ]. As such, we reasoned that a partial enhancement in microbial diversity by exposing laboratory mice to a “conventional” living environment might also augment immune and hematopoietic traits to better serve as models for the study of human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…As pointed out previously, the large majority of mouse studies use ST and SPF conditions [20]. These data suggest that maintaining bacterial diversity may prove beneficial to patients undergoing HSCT [72].…”
Section: Effect Of Housing Temperature On Survival and Tissue Damagesupporting
confidence: 53%
“…In addition to housing temperature, other environmental factors may significantly influence the onset and severity of other auto-and alloimmune diseases [20]. Li et al reported, using a similar model to the one described in the current study, that BM damage was significantly reduced in mice that were housed at ST under conventional conditions (CC) when compared to mice housed at ST in a standard barrier facility under specific pathogen-free (SPF) conditions [72]. Attenuated disease was associated with greater intestinal bacterial diversity in CC mice vs. that observed in the SPF group.…”
Section: Effect Of Housing Temperature On Survival and Tissue Damagementioning
confidence: 61%
“…This is not surprising given the evidence demonstrating that the intestinal microbiota of mice may vary greatly among different animal care facilities and animal vendors [74,75,[78][79][80]. Several laboratories including our own, have shown that the incidence and severity of chronic gut inflammation in different mouse models of inflammatory bowel disease is markedly altered by changing animal care facilities or by purposely altering the gut bacteria [81][82][83][84][85][86][87].…”
Section: Modulation Of Immunity and Inflammation By The Microbiomementioning
confidence: 99%